AFRICANS QUEST FOR IDENTITY IN NNEDI OKORAFOR’S THE BOOK OF PHOENIX - Jevisha.V; D.L. Jaisy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Nnedi Okorafor’s The Book of Phoenix (2015) explores the complex and multifaceted journey of identity formation for Africans in a dystopian future. Through the narrative of Phoenix, a genetically modified being with extraordinary abilities, Okorafor delves into the theme of a quest for identity against oppressive systems. Phoenix's quest for identity is emblematic of a broader struggle faced by African descents, grappling with the remnants of colonialism and enslavement. The novel intertwines reality with futuristic science fiction, offering a unique perspectives on the survival and growth of African identities. Okorafor's work challenges the readers to reflect on the enduring impacts of historical injustices while celebrating the rich cultural heritages that persistently influence and alter the African identity in a globalised world.